Caracterização físico-hídrica do solo em duas subbacias hidrográficas do Rio Teles Pires, Sul da Amazônia brasileira - Moratelli, Francielli Aloisio (2021)
Monitoring soil quality through its hydro-physical attributes is important for assessing the impact of land use and occupation, as it allows for the diagnosis of environmental changes and the subsidization of appropriate actions for natural resource conservation. The purpose of this study was to characterize the hydro-physical attributes of soils under different uses and occupations in two hydrographic sub-basins of the Upper and Middle Teles Pires river known as Rio Caiabi and Rio Renato, respectively. The assessment was conducted from November 2019 to May 2020, during the rainy season. Soil samples with deformed and undisturbed structure were collected in three regions of the sub-basins (spring, middle, and mouth) at depths of 0,00-0.10, 0,10-0.20, and 0,20-0,40 m under three conditions of use and occupation of the soil: native forest (NF), pasture (PA), and tillage (TI). Particle size, particle density (Dp), soil density (Ds), total porosity (Pt), macroporosity (Ma), microporosity (Mi), water content at field capacity (θCC) and permanent wilting point (θPWP), saturated soil hydraulic conductivity (Ksat), and soil available water capacity (AWC) were all evaluated. The findings indicate that land use and occupation have a significant impact on the hydro-physical attributes of the soil. It was discovered that for the two hydrographic basins, soil under anthropized areas had lower hydrophysical quality than areas of native forest. The highest values of Ksat (159,08 mm h-1 ) were found in native forest in the Caiabi river basin. The soil under pasture and conventional tillage in the Renato and Caiabi river basins reduced the macroporosity (up to 0,07 m3 m-3 ), which is considered restrictive to plant development. Furthermore, there was an increase in soil density and, as a result, a decrease in total porosity in the soil under tillage and pasture, indicating that changes in soil attributes under conventional agricultural production systems can contribute to soil compaction, decreased water infiltration, and increased surface runoff, thus accelerating erosive processes.